2001
DOI: 10.1051/rnd:2001103
|View full text |Cite
|
Sign up to set email alerts
|

Relation between dietary lipid level and voluntary feed intake, growth, nutrient gain, lipid deposition and hepatic lipogenesis in rainbow trout

Abstract: -Four diets with differing lipid contents (15,20,25 or 30% DM) were tested on small (initial body weight: 27 g) and larger (IBW: 93 g) rainbow trout (Oncorhynchus mykiss) fed on demand or by hand, respectively. In both trials, voluntary feed intake was inversely related to dietary lipid levels. Protein efficiency increased when dietary fat content increased. Final whole-body lipid content was positively related to dietary lipid levels. The main sites of lipid storage were visceral adipose tissue and to a lesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
63
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 81 publications
22
63
3
4
Order By: Relevance
“…This was unexpected and inconsistent with the known phenomenon that feed intake in fish is regulated to meet their energy requirement (Boujard and Médale 1994;Grisdale-Helland and Helland 1997;Gélineau et al 2001;Wang et al 2005). It may be suggested that in shi drum, dietary protein plays more important role in the regulation of feed intake instead of dietary lipid or energy.…”
Section: Discussionmentioning
confidence: 87%
“…This was unexpected and inconsistent with the known phenomenon that feed intake in fish is regulated to meet their energy requirement (Boujard and Médale 1994;Grisdale-Helland and Helland 1997;Gélineau et al 2001;Wang et al 2005). It may be suggested that in shi drum, dietary protein plays more important role in the regulation of feed intake instead of dietary lipid or energy.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies on several species reported that the lipid content in fish muscles changes seasonally [35,36], and that cultured fish meat tends to contain more lipids [37][38][39]. A high-fat diet causes an increase in the lipid content of fish tissues [40][41][42], and short-term fasting causes an increase of lipid content in the muscle [43]. However, feeds with higher lipid content are more expensive.…”
Section: Discussionmentioning
confidence: 99%
“…For the feeds used in feed nutrition to cause less pollution, the required nitrogenphosphorus balance must be provided depending on the fish species and age. In aquaculture, by meeting the optimum protein and energy requirements of fish, waste feeds and nutrient losses can be prevented [7]. Furthermore, eutrophication can be prevented with polyculture applications (sea fish and crustaceans) [4].…”
Section: Feedingmentioning
confidence: 99%